What does it Take for a Successful Pension Scheme? - Fatemeh Kimiyaghalam (Journal of Social Science, 2023)
Labor market reform encompasses a wide range of issues aimed at increasing competitiveness, increasing productivity, and improving labor force lives. No issue, however, has been more critical than ensuring that the pension system delivers on its promises. This has been a major issue for the labor force, and it will continue to be so. Countries all over the world have made efforts to improve their pension systems. Some have privatized it in order to make it more efficient and less taxing on the government. The main objective of pension and retirement policies is to provide adequate income in old ages. Countries consider many elements to choose their pension system according to five pillar pension schemes. This paper tries to look at these different retirement plans around the world and to give an assessment of their characteristics. Using a simple model, it attempts to display the relationship between the type of pension system and its success. The findings of some simple pension reforms can be lightening the way for policymakers.